Revisiting the Oil-Growth Nexus : Evidence from Selected Oil Importing and Oil Exporting Countries - Chin, Kho Kian; Shirly Siew Ling, Wong (2022)
This study investigates the impact of oil prices on economic growth in oil importing countries (China, Germany, Italy, India, Japan, Netherlands, South Korea, Spain and Thailand) and oil exporting countries (Brazil, Canada, Iran, Kuwait, Mexico, Nigeria, Norway, Russia, Saudi Arabia and United Arab Emirates), covering the period of 1995- 2021. Under the panel estimation approach, we can postulate that oil price is exerting a significantly positive impact towards economic growth for oil exporting nations, regardless of whether the time horizon is in short run or long-run contexts. On the other hand, oil importing nations tend to experience negative impact from the oscillatory fluctuations in the oil price. It is proposed that policy makers in oil importing nations can respond to the positive oil price shock can be lessened by hedging product purchases using futures contracts on net oil-importing nations with poor exports of other commodities. Alternatively, for net oil-importers, pricing-based policies such as transferring price increases to consumers and providing subsidies can be implemented to reduce the negative effect of oil prices hikes towards the economy.